Transcriptomic analysis in blv-experimentally infected cattle leading to high or low proviral load - Juliarena, Marcela Alicia (2018)
Bovine Leukemia Virus (BLV) is a highly prevalent pathogen causing a fatal lymphoproliferative disease in the bovine species. Afterexperimental infection, proviral load peaks at 30 days post infection (dpi), then, cattle progress to two different phenotypes: one is characterizedby high proviral load (HPL) in peripheral blood, while the other is identified by low proviral load (LPL) in peripheral blood. In LPL cattle asharp decrease in proviral load is evidenced at 38 dpi. We studied the transcriptome in peripheral blood cells from 10 cattle (5 of each phenotype)infected with BLV at 38 dpi, to identify the host genes differentially expressed in those animals that progress to LPL, recognized as BLVresistant.RNA seq experiments showed 499 genes differentially expressed (p<0.05) between both phenotypes: 281 upregulated and 218downregulated in LPL compared to HPL cattle. Gene ontology analysis revealed that genes related to inflammatory response, humoral immuneresponse and leukocyte migration were up regulated in cattle progressing to LPL compared to HPL (p< 0.05), while the regulation of homeostaticprocess, antigen receptor signaling pathway and phospholipid transport were downregulated in LPL compared to HPL cattle (p< 0.05). The hugedifference in transcript expression found at 38 dpi, suggests that mechanisms used to control the proviral load are turned on early after theinfection, although the phenotype of LPL or HPL is established only after 90 dpi.